(untitled) (MAUSAM, 1965)
In association with a monsoon depression which recurved over east Rajasthan and moved northwards into Jammu Province, torrential rains occurred in the north Punjab and northwest Uttar Pradesh on 20 and 21 September 1962. This rainfall could not be explained in terms of the low level circulation of the depression alone, which was still far away, and was found to be associated with marked high level divergence in a deep layer extending from 500 to 200.mb levels. An examination of the peculiar features of the rainfall in different areas and the associated synoptic features has shown the relative importance of the three factors, low level convergence, moisture feed and high level divergence on the rainfall distribution.